Kebijakan Penggunaan Tenaga Kerja Asing Di Indonesia - Lalu Adhi Adha; Lalu Husni; Any Suryani (Fakultas Hukum Universitas Mataram, 2016)
Increased globalization encourage the movement of capital and investment flows across the world, there is also a migration of people or movement of labor between countries. The labor movement took place because of the investments made in other countries generally require direct supervision by the owner / investor. Correspondingly, in order to maintain continuity of business and investment. To avoid legal problems as well as the use of foreign labor is excessive, then the Government must carefully determine the policy (policy) to be taken in order to maintain a balance between foreign workers (foreign capital) with domestic labor. Therefore, in this paper, researchers have found -ketentuan legal provisions that have relevance for regulating the use of foreign labor and to analyze the regulation of keberlakuanya juridical aspects, As Intended use of foreign labor is to meet the needs of skilled workers and professionals in the field certain that can not be filled by the Indonesian labor and accelerate the process of national development by accelerating the transfer of knowledge and technology and increase foreign investment as supporting development in Indonesia. The results of this study certainly expected to be on particular subjects Employment Law at the Faculty of Law of the University of Mataram and, if possible, may be on the improvement of regulatory and policy issues -kebijakan the Utilization of Foreign Workers in Indonesia both national and local scale.